A Comparative Analysis of Cruise Ports on the Mediterranean: The Case of Istanbul - Kerestecioglu, Funda; Basdogan, Serhat (MEDITERRANEAN COASTAL FOUNDATION-MEDCOAST FOUNDATION, 2009)
As a historic coastal city and a commercial and cultural capital for nearly three thousand years, Istanbul has always had a direct connection with the seaside, where its citizens spent their daily lives. However, during the last decade, due to adjustment efforts for globalization and EU integration, Istanbul has exhibited a considerable restructuring of its social and physical environment. Direct foreign investments and land developments by the municipality intensify this process, especially along the coastal regions, since these are the most valuable parts of the city. This situation puts pressure on the city's coastal parts and affects redevelopment projects that are important for the quality of the urban environment regarding sustainability. Coastal regions within Istanbul have been reshaping under this conjuncture. When we look from the viewpoint of the tourism sector, Istanbul could not use its historical, cultural, and natural advantages to its maximum benefits when compared to other Mediterranean seaport cities. To meet expectations of the tourism sector, Istanbul needs new port and land management projects for cruise tourism. The main aim of this study is to determine criteria for new coastal developments in Istanbul and discuss location criteria for a new cruise port within the city, where the tourism sector can operate effectively without distorting the quality of the urban environment and the built heritage. Comparing the cruise destinations in the Mediterranean Basin will help further the establishment of integrated coastal zone management strategies for Istanbul's coastal zone usage.
Keywords: WATERFRONT REDEVELOPMENT; Engineering; Environmental Sciences & Ecology; Water Resources